Introduction to special section on: current topics in cancer survivorship and work - de Boer, A. G. E. M. (J Cancer Surviv, 2020)
ABSTRACT: Work is a key contributor to quality of life and an important aspect of cancer survivorship. We call attention to current topics in cancer survivorship and work with 12 articles on cancer survivorship and work in this special section. The focus is on less studied diagnostic groups such as gastrointestinal cancer and prostate cancer, and on long-term effects of cancer diagnosis and treatment on work. Furthermore, studies are included on topics not generally studied including cognitive limitations and pain, the role of the employer on work outcomes among different types of cancer survivors and some countries not typically covered in the existing literature on work and cancer survivorship. We conclude that to improve sustainable work participation in cancer survivors, personalised, tailored interventions should be provided. A prerequisite for this is the identification of groups and individuals at high risk for adverse work outcomes. In order to develop such interventions, research involving new approaches such as matching data registries, participatory approaches and the involvement of many stakeholders and survivors with these different types of cancer diagnoses is necessary. IMPLICATIONS FOR CANCER SURVIVORS: The goal of sustainable work participation in cancer survivors can be improved by the delivery of a personalised or risk-based tailored intervention. Furthermore, successful work outcomes often involve many stakeholders who should all be included Implications for Cancer Survivors. The goal of sustainable work participation in cancer survivors can be improved by the delivery of a personalised or risk-based tailored intervention. Furthermore, successful work outcomes often involve many stakeholders who should all be included.